Kounis Syndrome: Myocardial Infarction After Wasp Bites - E. D. Resnyanskaya; D. S. Evdokimov; V. S. Feoktistova (Архивъ внутренней медицины)
The presented clinical case describes a rather rare type II Kunis syndrome (SC) that occurred in a 69-year-old man with risk factors for coronary heart disease (CHD) after wasp bites and was accompanied by the development of acute myocardial infarction (MI) due to coronary artery thrombosis (CA). The diagnosis of MI was confirmed on the basis of laboratory and instrumental data: an increase in troponin levels (>10000 pg/ml), changes in the electrocardiogram (ECG) (elevation of the ST segment in II, III leads, aVF), revealed violations of the contractility of the left ventricle (LV) according to echocardiography (zone of akinesia of the basal lower segment LV, hypokinesia of the median inferior and anterolateral segments of the LV, the apical-lateral segment of the LV), the results of coronary angiography (acute occlusion with signs of parietal thrombosis in the right coronary artery). The cause of CA thrombosis could be either a pronounced immuno-inflammatory reaction or the administration of adrenaline to stop anaphylactic reaction. Currently, there are no clear criteria for the verification of SC, the diagnosis is confirmed on the basis of a comprehensive examination of a patient with acute coronary syndrome (ACS) and the presence of a pronounced allergic/anaphylactic reaction. Additionally, to confirm the SC, it is proposed to assess the level of histamine and tryptase in the blood, however, these markers are metabolized quite quickly and, in most cases, it is not possible to identify their elevated levels. This case once again underlines the importance of informing doctors about the risk of developing ACS against the background of a pronounced allergic reaction, as well as the need for further study of SC in order to develop tactics for the treatment and prevention of this group of patients.